PENGARUH PEMBELAJARAN DALAM JARINGAN (DARING) TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN PKWU KELAS XI SMK NEGERI 4 KOTA JAMBI - Silvia, Melinda; Andriani, Lili (SJEE (Scientific Journals of Economic Education), 2021)
AbstractThis study aims to (1) find out the description of the application of online learning in the subjects of creative products and entrepreneurship at SMK Negeri 4 Jambi City (2) to find out student learning outcomes in the subjects of creative products and entrepreneurship in SMK Negeri 4 Jambi City. This research design uses survey research methods, with data collection techniques through observation and questionnaires. Where the population in this study were 89 students with a research sample of 73 students. The data management techniques in this research are Research Instrument Validity Test, Research Reliability Test, Quantitative Descriptive Analysis, Normality Test, Homogeneity Test, and Simple Regression Test. The results showed that (1) online learning obtained a TCR result of 66.81% with a fairly good category. (2) The calculation results obtained that student learning outcomes in the subjects of creative products and entrepreneurship scored less than 65 as many as 29 students and 39 students scored above the average of 73 samples (3) The results of the SPSS VERSION 16 calculation in simple regression obtained the regression equation Y=38,716 and regression X is equal to 0.413. The conclusion in this study is based on the data obtained that it is proven true, from the variables contained in this study can be used as a pedictor in knowing the effect of online learning (on the network) on student learning outcomes in creative products and entrepreneurship subjects.Keywords: Online Learning, Learning Outcomes